American ginseng tea protects cellular DNA within 2 h from consumption: results of a pilot study in healthy human volunteers. (3rd October 2015) - Szeto, Yim Tong; Sin, Yuk Shan Pauline; Pak, Sok Cheon; Kalle, Wouter
Abstract: The acute genoprotective effect of Panax quinquefolius (American ginseng) has been investigated. The experiment was carried out to explore the DNA protective effect after a single dose of American ginseng tea bag infusion. Fourteen subjects (6 males and 8 females) were recruited in this study. Seven of them (3 males and 4 females) were asked to drink a cup of freshly prepared American ginseng infusions. Water was taken by the remaining subjects as the control group. Blood samples of both groups were taken before and 2 h post-ingestion. The blood samples were challenged with ultraviolet B irradiation followed by using comet assay. Completed slides were stained with Giemsa stain and DNA damage was assessed. Results showed a significant decrease in comet score after American ginseng supplementation and no change in the control group. The current study demonstrated a cup of American ginseng infusion could protect cellular DNA from oxidative stress at least within 2 h.